PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN APLIKASI SHALAT FARDU SISWA - Nur Kholis (AS-SALAM, 2014)
Student’s ability to apply pray fardu good and correct is low, it can be seen from 20 students of one class only 4 students or 20 % of students who have been thoroughly studied. Students’ability to apply pray at Junior High School Islam Unggulan Miftaahul ‘Uluum is low The cause of problems in this research are method dan Media in teaching lerning used by teacher less interested dan still monotonically. This research aims to improve the application made by the students of seventh class at Junior High School Islam Miftaahul 'Uluum learning through used video kind of audiovisual media. The dependent variable (X) in this research is Applications of Student’s pray fardu, while the independent variables (Y) is a video kind of teaching learning audio visual media. Based on the results of research carried out showed that the type of video media audiovisual learning can improve application pray Fardu of the seventh class at junior high school Islam Unggulan Miftahul Ulum subject islamic education. This is evidenced by the increase in the average value of the application pray fardu students with an average 72.00 in the first cycle to 80.75 in the second cycle, the percentage increase in student applications pray fardu that is equal to 90% of the number of students.